2019
DOI: 10.1126/scitranslmed.aao5563
|View full text |Cite
|
Sign up to set email alerts
|

Teriflunomide treatment for multiple sclerosis modulates T cell mitochondrial respiration with affinity-dependent effects

Abstract: Interference with immune cell proliferation represents a successful treatment strategy in T cell–mediated autoimmune diseases such as rheumatoid arthritis and multiple sclerosis (MS). One prominent example is pharmacological inhibition of dihydroorotate dehydrogenase (DHODH), which mediates de novo pyrimidine synthesis in actively proliferating T and B lymphocytes. Within the TERIDYNAMIC clinical study, we observed that the DHODH inhibitor teriflunomide caused selective changes in T cell subset composition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 60 publications
3
95
2
Order By: Relevance
“…Altered levels and/or functional abnormalities in T or B cells have already been reported in patients with MS. 12,[19][20][21] However, previous studies are generally characterized by several limitations, including the focus on particular restricted immune cell subsets, small groups of patients mainly treated with a single DMT, 11,[22][23][24][25][26][27][28][29][30][31] different disease characteristics, lack of inclusion of controls, and difficult standardization of sample processing. 5,13,15,16 In this study, we have undertaken a large multicentric analysis of the immunologic profile of T and B cells in a cohort of 227 patients with MS at different disease stages treated with different DMTs and 82 HCs.…”
Section: Discussionmentioning
confidence: 99%
“…Altered levels and/or functional abnormalities in T or B cells have already been reported in patients with MS. 12,[19][20][21] However, previous studies are generally characterized by several limitations, including the focus on particular restricted immune cell subsets, small groups of patients mainly treated with a single DMT, 11,[22][23][24][25][26][27][28][29][30][31] different disease characteristics, lack of inclusion of controls, and difficult standardization of sample processing. 5,13,15,16 In this study, we have undertaken a large multicentric analysis of the immunologic profile of T and B cells in a cohort of 227 patients with MS at different disease stages treated with different DMTs and 82 HCs.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of T cells have difference in their metabolism, and targeting components of the metabolic machinery can be a way to selectively eliminate T cells [30]. Recently, it was demonstrated that the drug Teriflunimide, an inhibitor of the enzyme dihydroorotate dehydrogenase (DHODH) involved in de novo pyrimidine synthesis, causes selective changes in T cell subset composition and TCR repertoire diversity in patients with relapsing-remitting MS [31]. It was demonstrated that DHODH inhibition mechanistically interfered with oxidative phosphorylation (OXPHOS) and aerobic glycolysis in activated T cells via functional inhibition of complex III of the respiratory chain, and that the effect on T cell proliferation was closely linked to antigen affinity of the T cell clones.…”
Section: Antigen-specific Therapies Aiming At T Cell Clonal Deletionmentioning
confidence: 99%
“…However, to elucidate the exact site(s) of action of teri and additional impact of abcg2, further experiments including conditional and chimeric animal models are needed as well as experiments on potential functional redundancy. Furthermore, abcg2-dependent effects on pleiotropic mechanisms of action of teri (i.e., T cell mitochondrial respiration [11];) with emphasis on teri concentrations within cell organelles would be interesting to investigate. However, these aspects were beyond the scope of the current study which set out to investigate if abcg2 has an effect on teri-treatment in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicates that in the animal model, therapeutic modulation of teri efficacy in abcg2-KO mice is not associated with a modulation of peripheral T cell populations. In MS patients treated with teri and in rodents suffering from EAE treated with the respective prodrug leflunomide, it was demonstrated that different T cell populations were selectively affected with a preferential reduction in Th1 effector cells [11]. The differences observed may be explained by different drugs, treatment duration, or therapeutic setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation